IMPROVEMENT STRATEGY FOR OPEN GOVERNMENT DATA USING FUZZY AHP: CASE STUDY JAKARTA OPEN DATA - Pradipta, Dhea Junestya; Ariani, Septi; Sensuse, Dana Indra; Lusa, Sofian; Prima, Pudy (Masyarakat Telematika Dan Informasi : Jurnal Penelitian Teknologi Informasi dan Komunikasi, 2020)
Open Government Data (OGD) implementation provides benefits for government performance and public services. Based on the Indonesian government's openness action plan 2018-2020, the importance of monitoring and evaluation of OGD implementation for sustainable development is emphasized. This study aims to prioritize criteria and provide recommendations for OGD evaluations at the Jakarta Open Data. Through the mix method approach, expert interviews have been conducted to test the validity of the criteria which then carried out the distribution of questionnaires to eleven expert respondents from five departments. The data is processed using the fuzzy-Analytic Hierarchy Process (AHP) to determine each weight on twenty criteria in four dimensions. The results of this study indicate that in the short term, OGD internal evaluations in the DKI Jakarta provincial government can be done by assessing eight main priority criteria, namely accuracy, completeness, compliance, understandability, timeliness, openness, functionality, and reliability which are then based on overall criteria. These results are the basis for discussion in the Data Forum and the establishment of Standard Operating Procedure (SOP) to assist and accelerate the process of collecting, processing, verifying and validating data from 51 regional work units. Externally, the Jakarta Open Data team can pay attention to the conditions of citizen engagement in the OGD and the existence of a Memorandum of Understanding (MoU) between relevant ministries or agencies that does not yet have data officers or information and documentation management officers for effective and efficient data processing